Epidemiology of birth defects based on a birth defects surveillance system in southwestern China and the associated risk factors - Peng, Zhenren; Wei, Jie; Chen, Biyan; Huang, Xiuning; Song, Pengshu; Liang, Lifang; He, Jiajia; Feng, Baoying; Que, Ting; Qin, Jie; Xie, Yu'an; Qiu, Xiaoxia; et al. (Frontiers in Pediatrics, 2023)
Background: Birth defects (BDs) are associated with many potential risk factors, and the causes of BDs are complex. Objectives: This study aimed to explore the epidemiological characteristics of BDs in Guangxi of China, and to explore the associated risk factors of BDs. Methods: BDs data of perinatal infants (PIs) were obtained from the Guangxi birth defects monitoring network (GXBDMN) from 2016 to 2020. Univariate Poisson regression was used to calculate the prevalence-rate ratios (PRR) to explore the changing trends of BDs prevalence by year and the correlation between the regarding of characteristics of BDs (including infant gender, maternal age, and quarter) and BDs. Clinical characteristics of PIs with BDs and their mothers’ general characteristics were documented and Spearman correlation analysis was used to explore the potential associated risk factors of BDs. Results: From 2016 to 2020, 44146 PIs were monitored being with BDs, with an overall BDs prevalence of 121.71 (95% CI: 120.58-122.84) per 10000 PIs, showing a significant increase trend (PRR = 1.116, 95% CI: 1.108-1.123), especially the prevalence of congenital heart defects (CHDs) increased most significantly (PRR = 1.300, 95% CI: 1.283-1.318). The 10 most common BDs were CHDs, polydactyly, congenital talipes equinovarus, other malformation of external ear, syndactyly, hypospadias, cleft lip with cleft palate, cleft lip, hemoglobin Bart's hydrops fetalis syndrome (BHFS), and congenital atresia of rectum and anus. BDs were positively correlated with pregnant women’s (R = 0.732, P < 0.01) and education level (R = 0.586, P < 0.05), and having pre-gestational diabetes mellitus (PGDM) / gestational diabetes mellitus (GDM) (R = 0.711, P < 0.01); while when the pregnant women had the family history of a dead fetus (R = -0.536, P < 0.05) and the birth of a fetus with BDs (R = -0.528, P < 0.05) were negatively correlated with BDs. Conclusion: A significant increase in the prevalence of BDs was detected from 2016 to 2020 in Guangxi, especially the prevalence of CHDs increased most significantly. Older maternal age, higher maternal education level, and with PGDM before pregnancy or GDM in early pregnancy were the risk factors for BDs.